Joubert syndrome with autism in two siblings: A rare presentation - Raghavan, D. Vijaya (Indian J Psychiatry, 2016)
Joubert syndrome is a rare autosomal recessive disorder with partial or complete agenesis of cerebellar vermis. This syndrome is identified mainly by the presence of molar tooth sign in magnetic resonance imaging of the brain since it has a varied phenotypic presentation. Of the 200 cases reported so far in the literature, only three reports show the presence of autistic symptoms in siblings suggesting a link between the cerebellar vermis and autistic spectrum disorders. In this case report of two siblings, the female child satisfied the criterion for autistic spectrum disorder in accordance with Diagnostic and Statistical Manual of Mental Disorders Fifth Editon. The boy showed developmental delay with autistic features (not amounting to diagnostic threshold). This report is important in that it adds evidence to the literature that abnormalities of cerebellum are involved in the cognitive development and autistic symptoms.